Clinical Distribution And Antibiotic Resistance Pattern Of Nonfermenting Gram Negative Bacilli. - S.JAYANTHI; M.JEYA (International Journal of Pharma and Bio Sciences, 2012)
Nonfermenting Gram negative bacilli (NFGNB) emerged as important nosocomial pathogen causing opportunistic infections. Aim of the study is to detect the clinical distribution and antibiotic resistant pattern of nonfermenting Gram negative bacilli isolated from the clinical samples and to detect Mettalobeta lactamase production by multidrug resistant isolates. A total of 6284 clinical samples were processed for the period of six months. The species of the NFGNB isolates were identified by API ID 32 GN system (bio merieux).Screening for Metallo beta lactamase (MBL) production by combined disc test method was done on the multidrug resistant isolates. Out of 6284 clinical samples 327 (5.2%) nonfermenting Gram negative bacilli were isolated. The split up of NFGNB were Pseudomonas aeruginosa 135(41.2%),Pseudomonas species other than P.aeruginosa were 91(27.8%), Acinetobacter species 88(26.9%) and others 13(3.9%). Multidrug resistant strains among these isolates were 129 (39.4%) and the metallo beta lactamase enzyme producers were 40 (31%).